Association of serum potassium time in target range with cardiovascular outcomes in patients with HFpEF - Yu Liu; Jianping Bin; Yating Tang; Yanmei Chen; Wenlong Xu; Yuegang Wang; Zhiwen Xiao; Yingxuan Li; Xingqiao Chen; Fengling He; Haoxiang Huang; Chuling Li; et al. (Open Heart)
Background Serum potassium (sK) disorders are associated with worse outcomes in patients with heart failure with preserved ejection fraction (HFpEF). This study introduced a novel metric, time in target range (TTR), for long-term monitoring of sK levels and determined its prognostic value in patients with HFpEF from the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) trial.Methods The TTR for sK levels was defined as the percentage of time during which the sK was within the target range of 4.3–4.9 mmol/L, and was estimated using linear interpolation based on at least five valid measurements of sK. The association between sK TTR and cardiovascular (CV) events was estimated using adjusted Cox proportional hazards regression models.Results A total of 3141 TOPCAT participants with HFpEF were evaluated over a median follow-up period of 3.9 years. A greater time within the range of 4.3–4.9 mmol/L for sK was associated with a lower risk of CV events in patients with HFpEF (HR: 0.712; 95% CI: 0.571 to 0.889). The benefits remained when the range of sK was set at 4.3–4.6, or 4.6–4.9, while no benefits or even negative effects were observed at 4.0–4.3, or 4.9–5.2 mmol/L. The association between a higher TTR and lower risk of CV outcomes was consistent across subgroups. The sK TTR predicted a lower risk of CV events, even after adjusting for traditional CV risk factors, mean sK and sK variability.Conclusion Maintaining sK levels within the range of 4.3–4.9 mmol/L most of the time in patients with HFpEF is associated with a lower risk of CV events or all-cause mortality.Trial registration number NCT00094302.